HUBUNGAN ANTARA KOMUNIKASI TELEMARKETING ASURANSI DENGAN SIKAP CALON PELANGGAN TERHADAP TELEMARKETER [Relations Between Insurance Telemarketing Communication and Potential Customer’s Attitude Towards Telemarketers] - Rut Rismanta Silalahi; Witanti Prihatiningsih; Ratu Laura M P B (Metacommunication, 2018)
ABSTRACT                 Telemarketing of insurance products is used by many companies because it is considered as simple, inexpensive and effective way to reach more customer. However, the potential customer may have different attitudes toward this method. They may be happy to receive such calls, but some of them might feel annoyed and inconvenienced. This study aims to find out whether there is a relation between insurance telemarketing communication and potential customer's attitude towards telemarketers. Using Instrumental Model of Persuasion, we took two factors into account: telemarketer as source factor and content of the call as message factor. The population of this quantitative research is potential customer who had been called by insurance telemarketers in Jakarta. We used snowball sampling technique and collected data through observation, questionnaire, interview and literature study. As the result, we found a significant and strong relation between insurance telemarketers and the attitude of potential customers. There is also a significant relation between messages delivered by telemarketers and the attitudes of potential customers, but with weak coefficient of closeness.Keywords:  Telemarketing Communication, Telemarketer, Attitudes, Instrumental Model of Persuasion.